PERFORMANCE OF POLYVOLTINE X BIVOLTINE (PURE MYSORE X CSR2) HYBRIDS OF THE SILKWORM BOMB YX MORI L. - PURUSHOTHAM, S.; RAO, P. RAMA MOHANA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
For one year cross-breed hybrid crops of the silkworm Bombyxmon L in Ananthapur District of Andhra Pradesh were observed and data were collected from 3255 crops covering all the seasons. Data indicate an average cocoon yield of 47.86 kg/lOO disease free layings (dfls). November to February is the most suitable period for silkworm rearing. Cocoon yield data during these months recorded an average yield of 50.6 to 52.62 kg! 100 dfls. April to May is generally not congenial for the silkworm rearing. Farmers were grouped based on the yield obtained and it was found that 47.86% of the farmers recorded an average cocoon yield of 40-60 kg! 100 dfls.,where as only 30% of the farmers recorded cocoon yield more than 60 kg/lOOdfls. Further, farmers were also grouped based on the dfls. intake capacity and found that farmers whose capacity was below 50 dfls/batch recorded higher yield (63.5 kg! 100 dfls) and farmers whose in take of dfls. were more than 150 dfls/batch recorded lower yields (24.08 to 36.18 kg! 100 dfls).